2013
DOI: 10.3174/ajnr.a3424
|View full text |Cite
|
Sign up to set email alerts
|

In Not Only Vertebroplasty but Also Kyphoplasty, the Resolution of Vertebral Deformities Depends on Vertebral Mobility

Abstract: BACKGROUND AND PURPOSE:It has not been clarified whether the postoperative resolution of vertebral deformities achieved by KP are superior to those achieved by VP. We compared the outcomes of KP and VP, taking into account the presence of vertebral mobility, to determine whether the balloon inflation in KP may contribute to postoperative resolution of the vertebral deformities in patients with VCFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…17 , 26 – 56 ( Figure 1 ). They included 4 RCTs, 27 , 31 , 41 , 53 14 prospective cohort studiess, 17 , 32 , 33 , 36 , 39 , 40 , 41 49 , 54 and 14 retrospective cohort studies 26 , 28 30 , 34 , 35 , 37 , 38 , 42 , 50 – 52 , 55 , 56 ( Figures 2 and 3 ). There were a total of 3274 patients; 1653 patients underwent the KP surgery and 1621 underwent VP surgery.…”
Section: Resultsmentioning
confidence: 99%
“…17 , 26 – 56 ( Figure 1 ). They included 4 RCTs, 27 , 31 , 41 , 53 14 prospective cohort studiess, 17 , 32 , 33 , 36 , 39 , 40 , 41 49 , 54 and 14 retrospective cohort studies 26 , 28 30 , 34 , 35 , 37 , 38 , 42 , 50 – 52 , 55 , 56 ( Figures 2 and 3 ). There were a total of 3274 patients; 1653 patients underwent the KP surgery and 1621 underwent VP surgery.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis found improvements in pain intensity, vertebral height, sagittal alignment, functional capacity, and quality of life with BK as compared with conventional medical management [75]. Multiple other studies demonstrated the benefit of VA for alignment with improvement in pain relief [19,[76][77][78], and respiratory function [79][80][81]. In a multisociety position statement, it was concluded that VA of osteoporotic VCF is clearly beneficial in the short term and likely beneficial also in the long term [33].…”
Section: Discussion Of Procedures By Variant Variant 1: New Symptomatmentioning
confidence: 99%
“…This results in decreased respiratory capacity by 25% to 50% [16]. Multiple studies have demonstrated the benefit of VA for alignment with improvement in pain relief [19,[76][77][78] and respiratory function [79][80][81]. Multidisciplinary case discussion is warranted prior to intervention.…”
Section: Variant 7: Pathologic Spinal Fracture With Spinal Deformity mentioning
confidence: 99%
“…Reduction of kyphosis with KP varies from 3.7° to 8° (mean 4.8°) whereas with VP it ranges from 0.5° to 3° (mean 1.7°) [10]. While some surgeons view that postural reduction is the most critical factor determining kyphotic postprocedural correction [5658], or claiming equivalent (or superior) results with nonballoon KPs [59, 60], other authors [61] as well as the extensive literature documentation with balloon KPs stresses the fact that balloon inflation also plays a role. Another important issue is whether this degree of kyphotic reduction correlates with clinical improvement.…”
Section: Vaps and Kyphotic Reduction/vertebral Height Restorationmentioning
confidence: 99%